Pharmacokinetic Parameters of Ciprofloxacin in Bangladeshi Volunteers: A Preliminary Evaluation - Chowdhury, Reefat Zaman; Islam, Md Saiful; Rahman, Md Sayedur (Bangladesh Journal of Physiology and Pharmacology, 2014)
The present study has attempted to establish a High-performance liquid chromatography (HPLC) method to determine ciprofloxacin in plasma, in order to evaluate the bioavailability of ciprofloxacin. In this study, initially 8 (eight) Bangladeshi Bangalee healthy male volunteers and 7 (seven) Bangladeshi Tribal healthy male volunteers received 500 mg tablet of pioneer brand of ciprofloxacin in oral route. Blood samples were collected at 0, 30, 60, 120, 180, 360, 540 and 720 minutes after drug administration. After 1 week of washout period, same volunteers of two groups received 200 mg injection of pioneer brand of ciprofloxacin in intravenous route. HPLC with ultraviolet detection was used to quantify plasma ciprofloxacin concentrations. In case of oral route, AUC012h, Cmax, Tmax and T1/2 values for Bangladeshi Bangalee and Tribal healthy volunteers were 545.53 ± 32.35 & 655.74 ± 16.57 ?g min/mL, 2.19 ± 0.16 & 2.49 ± 0.20 ?g/mL, 75.00 ± 27.77 & 94.29 ± 32.07 min and 241.96 ± 13.53 & 242.02 ± 19.88 min respectively. In case of intravenous route, the AUC012h, Cmax, Tmax and T1/2 values for Bangladeshi Bangalee and Tribal healthy volunteers were 344.07 ± 29.31 & 343.31 ± 25.34 ?g min/mL, 2.47 ± 0.17 & 2.46 ± 0.18 ?g/mL, 30.00 ± 0.00 & 30.0 ± 0.0 min and 278.16 ± 1.74 & 272.74 ± 4.42 min respectively and the difference between these two groups of volunteers was not significant. The difference in AUC012h, Cmax, Tmax and T1/2 values between these two groups of volunteers was significant. The mean percent absolute bioavailability in Bangladeshi Bangalee and Tribal healthy volunteers was 64.04 ± 3.21 and 76.81 ± 6.71 respectively. In conclusion, pharmacokinetic parameters of ciprofloxacin significantly varied among Bangladeshi Bangalee and Bangladeshi Tribal healthy volunteers indicating necessity of further study on population pharmacokinetic in these groups of people. DOI: http://dx.doi.org/10.3329/bjpp.v27i1-2.20066 Bangladesh J Physiol Pharmacol 2011;27(1&2):1-8.